2003
DOI: 10.1021/jp027582m
|View full text |Cite
|
Sign up to set email alerts
|

In Situ FT-IR Spectroscopic Studies of CO Adsorption on Fresh Mo2C/Al2O3Catalyst

Abstract: The surface sites of supported molybdenum carbide catalyst derived from different synthesis stages have been studied by in situ FT-IR spectroscopy using CO as the probe molecule. Adsorbed CO on the reduced passivated Mo 2 C/Al 2 O 3 catalyst gives a main band at 2180 cm -1 , which can be assigned to linearly adsorbed CO on Mo 4+ sites. The IR results show that the surface of reduced passivated sample is dominated by molybdenum oxycarbide. However, a characteristic IR band at 2054 cm -1 was observed for the ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 50 publications
(96 reference statements)
3
69
0
Order By: Relevance
“…It is suggested that the adsorption behavior of CO on the surface Mo of fresh molybdenum phosphide is greatly modified by the presence of P atoms, which distinguishes the surface properties of molybdenum phosphide from those of metallic molybdenum and molybdenum oxides. This is also found in the cases of molybdenum nitride [28,29] and carbide [40].…”
Section: Surface Sites Of Mop/siosupporting
confidence: 56%
“…It is suggested that the adsorption behavior of CO on the surface Mo of fresh molybdenum phosphide is greatly modified by the presence of P atoms, which distinguishes the surface properties of molybdenum phosphide from those of metallic molybdenum and molybdenum oxides. This is also found in the cases of molybdenum nitride [28,29] and carbide [40].…”
Section: Surface Sites Of Mop/siosupporting
confidence: 56%
“…29,30 It has been proposed that a thin layer of protective oxycarbide is formed when mild oxidants such as CO 2 or H 2 O are used; the extent of surface oxidation when O 2 is used for passivation is more difficult to control.…”
Section: Resultsmentioning
confidence: 99%
“…1a), corresponding to the adsorbed CO on the surface Mo sites and active carbon species, respectively. 15 When H 2 S was introduced onto the fresh sample preadsorbed with CO (Fig. 1b).…”
Section: Methodsmentioning
confidence: 99%